The Role of Marketing Strategy in Efforts to Increase Product Sales (Songket Fabric) on Traditional Gedongan Weaving, Dompu Regency-NTB - Mahmud Mahmud; Puji Handayati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Role of Marketing Strategy in Efforts to Increase Product Sales (Songket Fabric) on Traditional Gedongan Weaving in Ranggo Village, Pajo District, Dompu Regency, NTB. In the face of increasingly fierce and complex business competition, this includes changes in the company's strategy for distributing or marketing its products. A very important marketing activity by the company is how its products can be distributed and right on target with a good marketing strategy. The owner of the industry which is one of the systems that prioritizes communication where marketing is directed to consumers by providing information, promotion and persuading and reminding the target market of the company and the products offered to be willing to accept, buy, and be loyal to the products being marketed. There are several ways to do marketing activities, namely by direct and indirect, although each has its own advantages and disadvantages. Marketing Strategy of Traditional Gedongan Woven Products, namely, having an important role in the duties and obligations of helping sell and coordinating the gedongan woven industry, which has been planned in advance, and as part of the gedongan woven industry equipment to increase the sales of the product/fabric. The product marketing strategy has an advantage in market competition, where before the above strategy was carried out the traditional gedongan woven company/industry was unable to reach the market. After implementing the product marketing strategy, the gedongan weaving company/industry is able to reach the market and increase its sales. Thus, based on the description above, the researcher can say that the role of marketing strategy in an effort to increase sales is very good and very important to implement.